Direction of Trade Statistics March 2015. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2015)
This issue of Direction of Trade Statistics Quarterly provide, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. The quarterly issues, yearbook, and CD-ROM of the Direction of Trade Statistics present, for most member countries of the IMF, current figures on the value of merchandise exports and imports disaggregated according to their most important trading partners. Aggregates for the World table are calculated as the sum of aggregates from the tables for the Advanced Economies and Emerging and Developing Economies. The information on exports and imports by trading partners that countries report to the IMF varies in terms of frequency and currentness. When information is not reported and is inadequate to support the estimation techniques, the data are extrapolated using a matrix of trade among broad country groups. No estimates, however, are compiled for periods prior to 1981 or based on benchmark data referring to 1980 or earlier.